Digital Transformation as Part of Hospital Marketing Strategy: Literature Review - Dyah Ayu Masita; Muhammad Zulfikar Asumta; Herin Mawarti; Achmad Zakaria (Indonesian Journal of Global Health Research, 2025)
The number of clients of advanced communication instruments proceeds to extend, so most showcasing techniques utilize different web stages and social media. Advanced media is utilized as a shape of promoting communication not as it were by item fabricating companies but moreover by the healthcare segment, especially hospitals. Advanced change within the healthcare division is executed through a technology-based approach to move forward patient-centered healthcare administrations. The reason of this writing survey is to depict advanced change as portion of promoting methodology. This article employments the writing audit strategy to survey writing distributed in English and Indonesian. The taking after databases were utilized for the writing look: Pubmed, ProQuest, ScieneDirect, and Google Researcher. The information utilized in this consider are auxiliary information. This implies that they were not obtainedfrom coordinate perception, but or maybe from ponders conducted by past analysts. Healing centers must lock in in computerized change, counting compelling advanced promoting, to advance therapeutic administrations as portion of commerce development, give quality restorative administrations, and guarantee understanding fulfillment. Social media could be a computerized promoting stage broadly utilized by healthcare organizations.